The Effect of Macroeconomic Variables and Special Banking Characteristics on Non-Performing Loans in Iranian Banking System - Teymour Mohammadi; Farzad i Eskandar; Davoud Karimi (Faslnāmah-i Pizhūhish/Nāmah-i Iqtisādī, 2016)
The purpose of this study is to investigate the effects of macroeconomic and bank-specific factors on non-performing loans for the period of 2005 to 2013. A dynamic panel data model is used in 18 banks and to assess non-performing loan, the ratio of non-performing loans to all granted loans has been utilized. The results of Generalized Method of Moments (GMM) indicate that among all considered macroeconomic variables, economic growth has a negative effect, the gap between real interest rate in informal market and the real interest rate in formal market and also exchange volatility have positive effect on the ratio of NPLs to all granted loans. The results of bank-specific factors show that capital adequacy ratio, deposit to expenditure ratio, as an indication of economic efficiency, and share of each bank in total loans granted, as a proxy for banks' size, all have a significant negative influence on non-performing loans. The result confirms that “Bad Management hypothesis”, in which the increase of total expenditure efficiency leads to reduction in non-performing loans and “Market Strength and Stability hypothesis”, in which the banks with higher market power has less due date non-performing loans are both confirmed.